The use of brand and masculinity archetypes in analysing consumer engagement in advertising - Toms Kreicbergs; Deniss Ščeulovs (Trends Economics and Management, 2022)
Purpose of the article: To review recent research into the connection between brand archetypes and masculinity archetypes in advertising and assess them from a consumer engagement perspective. The study focused primarily on two main questions. The first was to find out which brand archetypes and masculinity archetypes are the most common in advertisements concentrating on traditional and modern masculinity. The second main question was to find out which brand and masculinity archetypes get more approval from the consumers and which have more positive feedback. Methodology/methods: The researchers used qualitative content analysis, video content analysis, and sentiment analysis. The qualitative content analysis was conducted using the Nvivo 11 qualitative data analysis software to help organise, analyse, and find relevant insights in the text. The authors chose to have a mixed content analysis of conventional and direct content analysis. The qualitative content and sentiment analysis were used to analyse consumer opinions from 2400 YouTube comments on certain advertisements where masculinity is identified as a critical concept. Scientific aim: To see whether the brand archetype theory and masculinity archetype theory are compatible in analysing consumer opinions about masculinity advertisements. Findings: The results from the video content analysis show that the most common brand archetypes in masculinity advertisements are the Caregiver, Ruler, Lover, and Hero. Regarding masculinity archetypes, the most common ones are the King, Lover, and Warrior. Conclusions: The most positive consumer discourse was for the advertisements with the Lover, Creator, Everyman, Explorer, and Hero brand archetypes. Concerning masculinity archetypes, the most positive consumer discourse was with the Lover and Warrior masculinity archetypes.
Keywords: M37; M31; 650; Brand; Archetype; Masculinity; Advertising; Marketing